The Public Health Campaign: A Literature Review from the Point of Use of Media and Communication in Malaysia - Raja Ismail Shaleh (International Journal of Science and Society, 2020)
This research describes the historical series of the occurrence of the Balkan Wars and the implications thereof for Muslim life there. This study took three main problems, namely (1) the causes of the Balkan Wars, (2) the chronology of the Balkan wars, and (3) What are the implications of the Balkan wars on the socio-political life of Islam in Southeast Europe. The research method used in this thesis is the historical research method. 4 stages, namely (1) Heuristics, (2) Source/Verification Criticism, (3) Interpretation and (4) Historiography. There are two approaches used in this study, namely the political and sociological approaches. While the theory I use in this research is theory. conflict and social change theory. The results of the research that the authors obtained are: chronologically, the Balkan war was preceded by the problem of Macedonia which in the end was used as an excuse to legitimize the war. Basically, the main cause of this Balkan war was due to the ambition and personal grudge between the respective rulers of the Balkan countries and the Ottoman Empire. It was also driven by the decline of the sultanate, Russian domination, the Turkish-Italian war (1911-1912), the idea of ​​nationalism, propaganda, the formation of the Balkan alliance and the failure of diplomacy. The outbreak of the Balkan war not only resulted in geo-political changes but also was a humanitarian catastrophe for Muslims in the Balkans who at that time had to accept the fact that their situation was no longer the same as when it was led by Muslims because authority had shifted to non-Muslims.